Control of Al-Hasa (Saudi Arabia) and direct contact with Britain, 1910 –1916 - ALMUTARI, MOHAMMED (Journal of Humanities & Social Sciences, 2018)
During the period of 1910-1916, in the times of annexing al-Hasa,  the Kingdom of Saudi Arabia (KSA) witnessed various relationships that contributed to its current face. The relationship between the KSA and Britain was amongst the prominent relationships in that era. In this context, the current study aims to investigate the annexation of the al-Hasa under the rule of Ibn Saud and into direct contact with the British, Ibn Saud's relationship with the Ottomans, and the role of Captain William Henry Shakespeare in the evolution of Anglo–Saudi relations. Besides, it attempts to clarify the relationship between the Ottoman Empire and Saudi Arabia, specifically, where this relationship came about to realize the strategic interests of both sides in the middle of the Arabian Peninsula.
Keywords: Saudi Arabia; al-Hasa; Britain; Ottoman Empire; William Henry Shakespeare